DYNAMIC SYSTEMS DEVELOPMENT METHOD DALAM PERANCANGAN SISTEM DARING KERAJINAN KHAS DAERAH - M Marfuah; I Irfan (JURNAL INFORMATIKA DAN KOMPUTER, 2018)
Various kinds of potential are owned by a community, especially Batam as a target of tourist destination. One potential that continues to be fostered is regional crafts that realize the economic independence of the community itself. The Government partner that have some programs to foster and develop regional handicraft products is National Craft Council of Batam under the guidance of the Industry and Trade Office. There are some obstacles faced by the management of traditional handicrafts, in term of promotion since it has been carried out in the exhibitions that are limited by time and place. It makes the development of the promotion and their potential run slowly in terms of disseminating information. It becomes the basic consideration for an online system of traditional crafts that prioritizes speed, easiness, flexibility and interactivity for some system users. Dynamic Systems Development Method (DSDM) is part of the agile software method. This method helps users to define clearly the system needs through early and continuous software delivery. The iteration in the design process makes it easier to adjust the needs of system users. The results of the system design are adjustments to the functional requirements of the system in accordance with the user needs.